Reagent Method For Wastewater Treatment In Textile Industries - D.J., Jumaeva; L.G, Aymurzaeva; I.D., Eshmetov; D.S, Salikhanova; B.A., Jumabaev (International Journal of Psychosocial Rehabilitation, 2020)
This paper makes analyses of the reagent method for wastewater treatment in textile industries. On this case, analyses have been discussed both methodological and theoretical bases. In conclusion, research has been pinpointed outcomes and shortcomings of the issue with the recommendations for further.